A Project-based Learning curricular approach in a Production Engineering Program - Simone Borges Simão Monteiro; Ana Carla Bittencourt Reis; João Mello da Silva; João Carlos Felix Souza (Production)
Abstract The Industrial Engineering undergraduate program offered at the University of Brasília was structured on Project Based Learning (PBL) methodology. This innovative educational proposal allows the students to deploy their technical competencies through real problem solving situations. The methodology also stimulates the development of the students’ soft skills, by exposing them to a challenging environment. At the end of each project, the results are presented to an external agent, and are subsequently implemented. The objective of this paper is to present the evolution of the PSP courses, which adopt as guidelines both the PMBOK project management framework, as well as content from specific technical courses related to the project’s subject. One other relevant aspect of the PSP courses is their involvement of both undergraduate and graduate students from different Engineering areas, such as Industrial, Mechanical and Civil Engineering, which serves to foster a more holistic and integrated problem-solving skillset.